Implementation of the Reasoning Training Program for Optimizing the UTBK Test at SMAN 1 Parepare - Rahmi, Nur; Ekasasmita, Wahyuni; Adhalia H., Nurul Fuady; S, Ahmad Fajri; Miftahulkhairah, Miftahulkhairah; Sarmila, Sarmila; Yusuf, Muh. (Jurnal Pengabdian UNDIKMA, 2023)
This community serviceÂ  aims to analyze and evaluate the implementation of a reasoning training program for optimizing the UTBK at SMAN 1 Parepare. The service involved 40 students from the twelfth grade who served as participants in the training program. The community service method used was quasi-experimental with a single-group pretest-posttest control design. The data analysis showed that the reasoning training program was effective in improving the UTBK results. There was a significant improvement in the average scores of the group that underwent the training compared to the control group. Additionally, the training program also assisted students in developing analytical and critical skills, which had a positive impact on their overall academic performance. This community service concludes that the implementation of the reasoning training program plays a crucial role in optimizing the UTBK at SMAN 1 Parepare. The results of this service contribute significantly to efforts to enhance student preparation for facing the UTBK and support their success in achieving better results in college admissions.